Corneal diameter and associated parameters in Chinese children: the Shandong Children Eye Study - Jiang, Wen Jun; Jonas, Jost B. (Clinical & experimental ophthalmology, 2017)
Background To assess the corneal diameter and its associations in children. Design Cross-sectional school-based study. Participants Six thousand twenty-six children aged 4-18 years were included in the Shandong Children Eye Study. Methods Horizontal corneal diameter was measured by laser interferometry-based ocular biometry. Main Outcome Measures Horizontal corneal diameter. Results Corneal diameter measurements were available for 5970 (99.1%) children. In multivariate analysis, larger horizontal corneal diameter (mean: 12.02 ± 0.38 mm; range: 10.1-15.0 mm) was associated with longer corneal curvature radius longer axial length, male gender, younger maternal age, rural region of habitation and lower intraocular pressure measurements. Higher prevalence of abnormally large corneas (macrocorneas; horizontal diameter ≥ 12.76 mm; mean value +2 × standard deviations; mean: 2.6%; 95% CI: 2.2, 3.0) was associated with longer corneal curvature radius, longer axial length, younger maternal age and male gender. Higher prevalence of abnormally small corneas (horizontal diameter ≤ 11.24mm; mean value −2 × standard deviations; mean: 2.4%; 95% CI: 2.0, 2.8) was correlated with shorter corneal curvature radius, shorter axial length and urban region of habitation. Neither abnormally large nor small corneas were correlated with time spent indoors/outdoors. Conclusions In 4 to 18-year-old children, larger corneal diameter was associated most strongly with flatter corneal curvature, followed by longer axial length and male gender. Corneal diameter was independent of age beyond an age of 4 years. Abnormally large and abnormally small corneas may be defined as being ≥12.76 and ≤11.24 mm in diameter, respectively. Corneal diameter was not correlated with time spent indoors/outdoors.